Product Placement On Indonesian Rap Song - Cokki; Sharon Nathania; Haris Maupa (Jurnal Manajemen, 2023)
Product placement literature has two gaps, namely research in developing countries including Indonesia and song as media placement. This study aims to fill this gap by testing the effectiveness of product placement in Indonesian rap songs on three aspects of consumer behaviour. The research design used pretest and post-test experiments without a control group involving 74 undergraduates as participants. The treatment used in this research is the song. It's a Dad Thing by Saykoji. The results showed that product placement on the song had an effect on brand recall, attitude towards the song and product placement influenced by attitude towards the artist, and purchase intention influenced by attitude toward product placement.